RESPON INVESTOR TERHADAP PERGANTIAN MENTERI KEUANGAN REPUBLIK INDONESIA PERIODE 20 MEI 2013 - Ridwan, Izaat Zakia (Department of Management, 2015)
The research aims to determine the response of stock investors to the changing of Republic Indonesia?s Finance Minister on 20th May 2013. Data used the company?s stock index in LQ45 2013. Technique of collecting data is using documentary methods. Data analysis is using event study, and statistics. The result shows that changing of Finance Minister Period 20th May 2013 does not have a significant impact on return and abnormal return to be earned by investors before, during, and after changing.